A MICROBLOGGING TO IMPROVE STUDENT CREATIVITY IN WRITING ACTIVITIES - Mohamad Sahril; Enni Erawati Saragih; Happy Riezky Stephano (Journal of English Language Learning, 2022)
Microblogging are often used by the teacher in the learning process. Microblogging like Instagram is one of the web technologies or applications that are used for the learning process. Microblogging is not only writing a tweet on Twitter. On Instagram students also can be media for student learning writing. In addition, microblogging can be used as interesting media to learn English. Therefore this study was conducted to find out what is a significant effect of using microblogging and also find out what are student perception of the use of microblogging to elevate student creativity in a writing activity. using qualitative methods, research instruments are interview, questionnaires, and documents. The study was conducted at one of the vocational school in Bogor with eight students as participants. From the findings, it is concluded that students have some significant and have positive perceptions after using microblogging in writing activities. Most students agreed that microblogging is easy to use for writing. They also said microblogging is an interesting medium for learning English. In addition, can motivate them to write better and elevate their creativity. Keyword: Microblogging, Creative Writing, EFL